The clinico-pathological effects of chicken infected with highly pathogenic avian influenza in some farms located in East Java and West Java - R Damayanti; NLP.I Dharmayanti; R Indriani; Achmad Selamet Wiyono; Darminto . (Jurnal Ilmu Ternak dan Veteriner, 2004)
The study was conducted to investigate the clinico-pathological features of highly contagious disease occurred in chicken located in East and West Java during the outbreak in September-October 2003. Six farms located in Districts of Surabaya, Malang and Blitar of East Java had been visited. They were mainly commercial layer, breeder layer and breeder broiler, which the population was between 14.000, 80.000, and aged 17-70 weeks. Where as five farms in West Java (Districts of Bogor, Bekasi and their surrounding areas) were visited and consisted of commercial layer and breeder broiler, having population of 3000-16.000 and aged 11-53 weeks. Observation was made according to clinical, gross pathological and histopathological changes. Clinically, most of them had cyanotic wattle and comb and subcutaneous petechiation of non-feathered part of the legs. These were also seen in necropsy, accompanied by general circulatory disturbances in most organs: namely pectoral and thigh muscle, trachea, lungs, epicard, myocard, proventriculus, liver, kidney and ovary. In addition, the liver was congested, friable and necrotic in some parts. Histologically, hemorrhage and non suppurative inflammatory reaction were observed in the brain, skin (comb, wattle and non feathered leg), skeletal muscle, trachea, lung, heart, proventriculus, liver, kidney and ovary whereas vasculitis was found especially in the skin of the wattle and comb, brain and kidney. It is concluded that based on the clinicopathological findings the outbreak of poultry disease in East and West Java were attributed to highly pathogenic avian influenza.   Key words: Highly pathogenic avian influenza (HPAI), chicken, clinico-pathology, outbreak, East Java, West Java